Impact of ESR1 Gene Polymorphisms on Migraine Susceptibility. Issue 35 (September 2015) - Li, Li; Liu, Ruozhuo; Dong, Zhao; Wang, Xiaolin; Yu, Shengyuan; Peng, Qi.
<x xml:space="preserve">Abstract</x> Abstract An increasing number of studies have explored genetic associations between the functionally important polymorphisms in estrogen receptor 1 (ESR1) gene and migraine susceptibility. The previously reported associations have nevertheless been inconsistent. The present work incorporating the published data derived from 8 publications was performed to assess the impact of these polymorphisms on incident migraine. Strength of the genetic risk was estimated by means of an odds ratio along with the 95% confidence interval (OR and 95% CI). From the results, we found individuals who harbored the 325-GG genotype, compared with those harboring the CC genotype or CG and CC combined genotypes, had almost 50% greater risk of migraine. The same genetic models showed notable associations in subgroups of Caucasians and migraine with aura (MA). For 594G>A, a moderately increased risk of migraine was seen under AG versus GG. The AA + AG versus GG model, however, showed a borderline association with migraine. Subgroup analyses according to ethnicity and subtype of migraine provided statistical evidence of significantly increased risk of migraine in Caucasians and of a marginal association with MA, respectively. Both 325C>G and 594G>A polymorphisms showed no major effects either in males or in females. Based on the statistical data, we conclude some of the ESR1 gene polymorphisms may have major contributions to the pathogenesis of migraine in Caucasian populations.